2022
DOI: 10.2340/actadv.v102.1993
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Brodalumab in Plaque Psoriasis: Integrated Pooled Data from Five Clinical Trials

Abstract: Brodalumab is approved for treatment of moderate-to-severe plaque psoriasis. Here, we assess the safety profile of brodalumab using pooled safety data from five Phase II/III trials of brodalumab 140 mg or 210 mg. In total, 4,464 patients received brodalumab, representing 8,891.6 patient-years of exposure. During the placebo-controlled 12-week induction period, rates of serious adverse events per 100 patient-years were 10.8 and 9.6 (brodalumab 140 mg and 210 mg, respectively) versus 4.3 and 6.5 (ustekinumab and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 27 publications
4
7
0
Order By: Relevance
“…patient-years) and MACE (0.2 per 100 patient-years), were low and similar to rates in a pooled analysis of five brodalumab trials 13 ; rates of serious infections and MACE were similar to those observed with secukinumab. 14 Rates of Candida infections were relatively low (4.5 per 100 patient-years in the 210 mg Constant group), but slightly higher than those observed with secukinumab (1.3 per 100 patient-years).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…patient-years) and MACE (0.2 per 100 patient-years), were low and similar to rates in a pooled analysis of five brodalumab trials 13 ; rates of serious infections and MACE were similar to those observed with secukinumab. 14 Rates of Candida infections were relatively low (4.5 per 100 patient-years in the 210 mg Constant group), but slightly higher than those observed with secukinumab (1.3 per 100 patient-years).…”
Section: Discussionsupporting
confidence: 74%
“…As expected, using imputation methods to account for missing data showed a lower percentage of responders compared to observed data; at Week 120, 49% of the 210 mg Constant group maintained PASI 90 and 40% maintained PASI 100 using the NRI/MAR imputation method. Rates of AEs of special interest in the 210 mg Constant group, including serious infections (1.5 per 100 patient‐years), Crohn’s disease (0.2 per 100 patient‐years) and MACE (0.2 per 100 patient‐years), were low and similar to rates in a pooled analysis of five brodalumab trials 13 ; rates of serious infections and MACE were similar to those observed with secukinumab 14 . Rates of Candida infections were relatively low (4.5 per 100 patient‐years in the 210 mg Constant group), but slightly higher than those observed with secukinumab (1.3 per 100 patient‐years) 14 .…”
Section: Discussionmentioning
confidence: 55%
“…As expected, this strategy is highly effective ( 70 ). The brodalumab clinical development program was abruptly interrupted for safety reasons (several cases of major adverse cardiovascular events in the brodalumab arm but not the placebo arm in one clinical study, resulting in a statistically significant safety signal) and subsequently resumed (brodalumab’s safety profile with regard to such major adverse cardiovascular events has recently been documented by an integrated safety analysis based on 5 clinical trials ( 71 ). Discontinuation of brodalumab treatment resulted in numerous relapses and even rebounds ( 72 ).…”
Section: Therapeutic Implications Of a More Detailed Understanding Of...mentioning
confidence: 99%
“…In the References section, the following are listed as sources for efficacy and safety data in pivotal studies of each biologic in and outside of Japan and for the results of the Japanese postmarketing surveillance of each biologic: infliximab, 9-18 adalimumab, [19][20][21][22][23][24][25] ustekinumab, [26][27][28][29][30][31][32][33][34] secukinumab, [35][36][37][38][39][40][41][42][43][44][45] ixekizumab, [46][47][48][49][50][51] brodalumab, [52][53][54][55][56][57][58][59][60] guselkumab, [61][62][63][64][65][66][67]…”
Section: Patients With Generalized Pustular Psoriasis (Gpp)mentioning
confidence: 99%
“…Table 1 shows the list of biologics available for psoriasis in Japan. In the References section, the following are listed as sources for efficacy and safety data in pivotal studies of each biologic in and outside of Japan and for the results of the Japanese post‐marketing surveillance of each biologic: infliximab, 9–18 adalimumab, 19–25 ustekinumab, 26–34 secukinumab, 35–45 ixekizumab, 46–51 brodalumab, 52–60 guselkumab, 61–68 risankuzumab, 69–72 certolizumab pegol, 73–77 tildorakizumab, 78–83 bimekizumab, 84–88 infliximab BS, 89,90 adalimumab BS 91 …”
Section: Eligible Patients For Treatment With Biologicsmentioning
confidence: 99%